'There is no "war on drugs"': An investigation into county line drug networks from the perspective of a London borough. (December 2021) - Bonning, John; Cleaver, Karen
County Line Drug Networks involve the transportation of drugs from urban hubs to out of city locations across the UK. County lines are a societal concern as they involve the recruitment of vulnerable individuals (adults and children), who are used as runners, exposing them to hazardous and often violent situations. This paper reports on a small scale study which provides a snapshot of the characteristics of nominals involved in county line drug network within a London Borough as well as the perspective of three expert practitioners who have substantial and detailed operational knowledge of how county line operatives work.